Plant Responses and Tolerance to Metal/Metalloid Toxicity (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue provides 15 research articles and 4 comprehensive review articles on various aspects of plant–metal/metalloid interactions. - Up-to-date information on plant responses to metals/metalloids are published. - Various mechanisms of plant tolerance to metals’/metalloids’ toxicity are presented. - Exogenous applications of mitigating metals’/metalloids’ toxicity are discussed. - Sustainable technologies in growing plants in metal/metalloid-contaminated environments are discussed. - Phytoremediation techniques for the remediation of metals/metalloids are discussed.